2021
DOI: 10.1111/tbed.14125
|View full text |Cite
|
Sign up to set email alerts
|

Shedding of Mycobacterium bovis in respiratory secretions of free‐ranging wild dogs ( Lycaon pictus ): Implications for intraspecies transmission

Abstract: It has recently been discovered that Mycobacterium bovis (M. bovis) causes disease in the endangered African wild dog (Lycaon pictus) in areas endemic for bovine tuberculosis (bTB), including the Kruger National Park (KNP). However, information on M. bovis infection dynamics within this species is limited and requires investigation as M. bovis can cause conservation consequences due to movement restrictions, crucial for genetic management. This study had two aims: firstly, to investigate mycobacterial shedding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Previous studies in African buffaloes have reported the high diversity of NTMs present in respiratory samples 23 . A study investigating M. bovis shedding in African wild dogs in KNP described a low percentage of M. bovis positive cultures (3.1–3.5%) of respiratory samples from IGRA positive individuals 17 , like findings in the current study. However, Parsons et al (2017) described a waning in QFT IGRA responses in three M. bovis experimentally infected white rhinoceros over time, with only a low IFNg in vitro response to purified protein derivative of M. avium 19 .…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Previous studies in African buffaloes have reported the high diversity of NTMs present in respiratory samples 23 . A study investigating M. bovis shedding in African wild dogs in KNP described a low percentage of M. bovis positive cultures (3.1–3.5%) of respiratory samples from IGRA positive individuals 17 , like findings in the current study. However, Parsons et al (2017) described a waning in QFT IGRA responses in three M. bovis experimentally infected white rhinoceros over time, with only a low IFNg in vitro response to purified protein derivative of M. avium 19 .…”
Section: Discussionsupporting
confidence: 81%
“…In a separate study of a human population with culture-confirmed M. tuberculosis infection (n = 80), M. tuberculosis DNA was detected in oral swabs from 29 (36.3%) individuals 36 . In a KNP population of African wild dogs ( Lycaon pictus ) with immunological sensitisation to M. bovis (determined using an IGRA) (n = 136), M. bovis was only recovered by conventional mycobacterial culture in 4 oronasal samples 17 . However, to our knowledge, this is the first report of M. bovis detection in nasal (swab) samples from African rhinoceros.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…tuberculosis DNA was detected in oral swabs from 29 (36.3%) individuals 36 . In a KNP population of African wild dogs (Lycaon pictus) with immunological sensitisation to M. bovis (determined using an IGRA) (n = 136), M. bovis was only recovered by conventional mycobacterial culture in 4 oronasal samples 17 . However, to our knowledge, this is the rst report of M. bovis detection in nasal (swab) samples from African rhinoceros.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the slow progression of disease, there are significant challenges in early detection of bTB in free-ranging wildlife, since most infected animals can shed viable mycobacteria before manifestation of visible clinical signs (Michel et al, 2006;Meiring et al, 2021). Therefore, to prevent the risk of introducing disease into new populations, movement of animals from endemic areas is restricted, unless there are accurate tests that can be used for screening.…”
Section: Introductionmentioning
confidence: 99%